AI, analytics and strategic decision-making - Ujwary-Gil, Anna, 1975-; Florek-Paszkowska, Anna (Routledge, 2025)
AI, Analytics and Strategic Decision-Making is an insightful exploration into the transformative power of artificial intelligence and advanced analytics in business and policy contexts. This volume provides a unique blend of theoretical knowledge and practical applications, showcasing how AI and analytics are reshaping decision-making processes across multiple domains.From predicting high-growth firms using Random Forests to leveraging Large Language Models for process mining, this book offers an extensive look at the latest innovations in AI and their strategic implications. It explores diverse topics, including the role of knowledge management in Industry 4.0, AI-powered decision-making tools for individuals, and public policy-making through Internet Public Opinion Analysis. Each chapter provides a nuanced perspective on how AI and analytics tools-ranging from Social Network Analysis to agent-based modeling-can tackle real-world challenges, such as climate change, resource allocation, and productivity enhancement.AI, Analytics and Strategic Decision-Making will inspire entrepreneurs, policymakers, academics, and business strategists to think critically about the power of data-driven insights and AI technologies. This comprehensive resource dives into how innovative tools can foster informed decision-making, drive efficiency, and pave the way for strategic success in an increasingly complex world.
Keywords: Artificial intelligence.; Decision making.; Strategic planning -- Technological innovations.; elektronické knihy; electronic books